2017
DOI: 10.20959/wjpr20178-9218
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of Turmeric – A Review

Abstract: Turmeric has been shown with wide spectrum of biological action which includes Anti-mutagenic, Anti-oxidant, Anti-inflammatory, Anti-diabetic, Anti bacterial, Anti viral, Hepatoprotective, Anti-fungal, Anti-protozoal, Anti-ulcer and Analgesic actions. Curcumin has the ability to inhibit carcinogenesis at three stages, namely tumour promotion, angiogenesis and tumour growth. Curcumin is also used topically to counteract inflammation and irritation associated with inflammatory skin conditions and allergies. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Studies have examined the antioxidant, hepatoprotective, cardioprotective, neuroprotective, antitumoral, and antimicrobial efficacy of this molecule across various administration routes and doses. [ 10 ] Research has demonstrated that 200 mg/kg enteral administration reduces liver injury in the steatohepatitis model induced by methionine-choline deficiency, 100 mg/kg intraperitoneal administration enhances liver regeneration, and 50 mg/kg intraperitoneal administration prevents H2O2-induced oxidative stress-related liver injury. [ 11 - 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have examined the antioxidant, hepatoprotective, cardioprotective, neuroprotective, antitumoral, and antimicrobial efficacy of this molecule across various administration routes and doses. [ 10 ] Research has demonstrated that 200 mg/kg enteral administration reduces liver injury in the steatohepatitis model induced by methionine-choline deficiency, 100 mg/kg intraperitoneal administration enhances liver regeneration, and 50 mg/kg intraperitoneal administration prevents H2O2-induced oxidative stress-related liver injury. [ 11 - 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Weight of oleoresin (g) Weight of sample (g) × 100 (5) where: Weight of oleoresin = (W 2 − W 1 ) g; W 1 = Weight of beaker with turmeric oleoresin content; W 2 = Weight of empty beaker.…”
Section: Oleoresin Contentmentioning
confidence: 99%
“…Its appearance is dark yellow and has a unique smell. Turmeric belongs to the Zingiberaceae family and is reported to possess numerous medicinal properties, including antioxidant [2], anti-protozoal [3,4], anti-tumor [5], anti-inflammatory [6] and antivenom activity [5,6]. The main component of Turmeric used in the pharmaceutical industry is curcuminoids, consisting of curcumin, demethoxy curcumin and bisdemethoxy curcumin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kulit batang jamblang diketahui memiliki kandungan flavonoid, asam ellagic, asam galat, friedelin, epi-friedelanol, βsitosterol, eugenin, ester asam lemak epifriedelanol, β-sitosterol, quercetin kaempferol, myricetin, dan bergenin [4]. Daun jamblang mengandung glikosida flavonol terasilasi, tanin, quersetin, triterpenoid, myricetin, myricetin 3-O-4-acetyl-L-rhamnopyranoside, galloyl carboxylase, dan esterase [5]. Daunnya banyak digunakan sebagai antidiabetes, sembelit, keputihan, demam, gastropati dan untuk menghambat keluarnya darah dalam tinja.…”
unclassified